ANALYSIS OF BANK INDONESIA RATE OF RETURN ON ASSETS AT THE PT. BANK MANDIRI TBK MANADO - Lalujan, Deisy Natalia; Pelleng, Frendy A.O.; Tumbel, Tinneke (Sam Ratulangi University, 2016)
ABSTRACT: This study aimed